NUMERICAL STUDY COMPARING THE INCIDENCE INFLUENCE BETWEEN REALISTIC WAVE AND REGULAR WAVE OVER AN OVERTOPPING DEVICE - Hübner, R. G.; Oleinik, P. H.; Marques, W. C.; Gomes, M. N.; Santos, E. D. dos; Machado, B. N.; Isoldi, L. A. (Revista de Engenharia Térmica, 2019)
This work presents a numerical study to evaluate the difference between the fluid dynamic behavior of an overtopping device subjected to the incidence of a realistic wave when compared to a regular one; being this regular wave representative of the considered realistic sea state. To do so, the FLUENT software was employed, which is a Computational Fluid Dynamics package based on the Finite Volume Method. The regular wave was generated through a User Defined Function (UDF) that imposes its velocities components as boundary conditions of prescribed velocity. On the other hand, for the realistic wave it was used a methodology to impose the realistic components velocities from transient discrete values, named Table Data (TD) in FLUENT software. For both cases the Volume of Fluid (VOF) multiphase model was applied in the treatment of the water-air interaction. The results showed that the amount of water accumulated in the reservoir for the realistic sea state was 2.46 higher than for the regular wave. This is a relevant finding, since several researches about Overtopping device efficiency were promoted considering only the incidence of regular wave.